REPLACR-mutagenesis, a one-step method for site-directed mutagenesis by recombineering - Ashutosh Trehan; Michał Kiełbus; Jakub Czapinski; Andrzej Stepulak; Ilpo Huhtaniemi; Adolfo Rivero-Müller (My University, 2022)
Mutagenesis is an important tool to study gene regulation, model disease-causing mutations and for functional characterisation of proteins. Most of the current methods for mutagenesis involve multiple step procedures. One of the most accurate methods for genetically altering DNA is recombineering, which uses bacteria expressing viral recombination proteins. Recently, the use of in vitro seamless assembly systems using purified enzymes for multiple-fragment cloning as well as mutagenesis is gaining ground. Although these in vitro isothermal reactions are useful when cloning multiple fragments, for site-directed mutagenesis it is unnecessary. Moreover, the use of purified enzymes in vitro is not only expensive but also more inaccurate than the high-fidelity recombination inside bacteria. Here we present a single-step method, named REPLACR-mutagenesis (Recombineering of Ends of linearised PLAsmids after PCR), for creating mutations (deletions, substitutions and additions) in plasmids by in vivo recombineering. REPLACR-mutagenesis only involves transformation of PCR products in bacteria expressing Red/ET recombineering proteins. Modifications in a variety of plasmids up to bacterial artificial chromosomes (BACs; 144 kb deletion) have been achieved by this method. The presented method is more robust, involves fewer steps and is cost-efficient.